Relationship between emotional intelligence and burnout: An empirical investigation of teacher educators - Ravi Kant; Amit Shanker (Institute of Advanced Engineering and Science, 2021)
Intention of this investigation was to explore if a relationship exists or not between emotional intelligence and burnout by examine a sample of 200 teacher educators that were selected by a purposive stratified sampling method from among of all teacher educators in District Gaya, India. In this investigation, two instruments were used to collect data, such as Weisinger’s Emotional Intelligence Test and Maslach Burnout Inventory (MBI). This research was correlation type so to analyze the data, were used Pearson correlation co-efficient and Analysis of Regression. Investigations found that teacher educator were not significantly different in emotional intelligence on the basis of gender, locality and teaching experience. Gender and teaching experience has nothing to play on burnout but locality has a significant difference on burnout score of teacher educators. Emotional intelligence and burnout syndrome have a strong negative association (r=-0.221), according to research results. Emotional intelligence had a significant contribution on burnout of teacher educators.